Societal conflict among relapsing male drug addicts in Cure and Care Service Centre, Kuala Pilah, Negeri Sembilan - Azizul, Muhammad Dhamir Audi; Wan Jaafar, Wan Munira; Mohd Khir, Azlina (Secholian Publication, 2018)
This social psychology study sought to understand how the inability of former drug addicts controlling interpersonal conflict that occurs in the community resulted in relapse or back to their addiction. A qualitative phenomenological approach was taken to conduct interviews with former drug addicts that are participating in a rehab program in Cure and Care Service Centre, Kuala Pilah, Negeri Sembilan, Malaysia. Eight informants were consented and interviewed. Purposive sampling was used and responses were analyzed thematically. These themes included the issue of labeling drug addicts as convicts, isolation from the community and restricted from participating in community-based programs. Researcher suggests related agencies to work with rehabilitation officers in restructuring the rehabilitation learning module and improve the interpersonal conflict management module. Therefore, it is hoped that in the future, former drug addicts would be capable to manage interpersonal conflict and simultaneously avoid from recidivism in addiction.